Analysis Factors of Willingness to Pay for Halal Labelled Cosmetics on Non-Muslim Community in Yogyakarta - Husnaa Winny Listyarini; Lilies Setiartiti (Universitas Muhammadiyah Yogyakarta, 2020)
This research aims to examine how product knowledge, promotion, consumers’ awareness, purchase frequency, and income influence on Willingness to Pay (WTP) for halal labelled cosmetics on non-Muslim community in Yogyakarta. This research used primary data with total 100 respondents by purposive sampling method. In addition, the analysis tool in this research are descriptive statistics, Contingent Valuation Method (CVM) which being used to predict willingness to pay, and multiple regression model on SPSS 20 as data analysis program. The result of this research shows that consumers’ awareness, purchase frequency, and income are positively and significantly influencing Willingness to Pay (WTP). And also the WTP value obtained for facial wash is Rp43.750, facial powder is Rp74.420, body wash is Rp31.670, toothpaste is Rp20.610, shampoo is Rp21.230, and body mist is Rp78.310.